Short-term prophylaxis with cefotaxime for prostatic surgery. Issue 6321 (3rd April 1982) - Hargreave, T B; Hindmarsh, J R; Elton, R; Chisholm, G D; Gould, J C
Abstract : A randomised controlled trial of a new cephalosporin, cefotaxime, was carried out in men undergoing transurethral resection of the prostate. The purpose of the trial was to determine whether 48-hour prophylaxis with this new broad-spectrum, non-nephrotoxic cephalosporin would reduce postoperative bacteriuria and postoperative complications. The treated patients fared significantly better than the non-treated patients in having fewer febrile episodes, fewer episodes of tachycardia, a lower incidence of appreciable bacteriuria postoperatively, and fewer complications, and spending on average one day less in hospital. There was no difference in postoperative urea and creatinine concentrations between the groups, and no other side effects of cefotaxime occurred in this elderly population. Prophylaxis with cefotaxime would appear to make prostatic surgery safer.